2021
DOI: 10.21109/kesmas.v16i1.4541
|View full text |Cite
|
Sign up to set email alerts
|

Junk Food Consumption and Symptoms of Mental Health Problems: A Meta-Analysis for Public Health Awareness

Abstract: Junk food consumption increases the risk of having symptoms of mental health problems. This study aimed to conduct a meta-analysis to assess the association between junk food and symptoms of mental health problems. Six researchers, two primary researchers, and four assistant researchers, from October to December 2020 conducted a systematic literature review. The data sources were selected from Pubmed and Science Direct articles published from 2010 to 2020. Those websites were check-marked for text availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Furthermore, the reduction in the contour index is associated with greater water absorption by the dough components, and a fraction that has a greater affinity for water is fiber, which is present in high content in the PDBB as reported in this research (Diedericks & Jideani, 2015; Gómez et al, 2010; Pathania & Kaur, 2022). However, this result does not indicate a low‐quality product, as cakes with PDBB can be a healthier snack option, among so many options prepared with excess saturated fats, salt, and sugars (Dias et al, 2015; Hafizurrachman & Hartono, 2021).…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the reduction in the contour index is associated with greater water absorption by the dough components, and a fraction that has a greater affinity for water is fiber, which is present in high content in the PDBB as reported in this research (Diedericks & Jideani, 2015; Gómez et al, 2010; Pathania & Kaur, 2022). However, this result does not indicate a low‐quality product, as cakes with PDBB can be a healthier snack option, among so many options prepared with excess saturated fats, salt, and sugars (Dias et al, 2015; Hafizurrachman & Hartono, 2021).…”
Section: Resultsmentioning
confidence: 95%
“…It is indicated that for improvement of mental health it is necessary to reduce the consumption of sugar and fatty foods. Fast food not only negatively affects mental health, but also impairs sleep quality (Hafizurrachman & Hartono, 2021;Kang, Kim, & Sunwoo, 2020). We did not determine a connection between the consumption of fast food and symptoms of depression.…”
Section: Discussionmentioning
confidence: 95%
“…The results of the report are no less surprising that there are still many university students who often eat fast food. Hafizurrachman [11] said that many studies mention the relationship between junk food or fast food and mental health problems is quite acute. Even small but frequent consumption of fast food or junk food can contribute to aggravated mental health symptoms.…”
Section: Resultsmentioning
confidence: 99%